Analysis of quality control issues in lakop sapu ijuk using Root Cause Analysis (RCA) - Evryan Yoga Arditya; Budi Nur Siswanto; Dudi Hendra Fachrudin (Universitas PGRI Madiun, 2023)
UD Cibinong Indah Plastik is engaged in the production of cleaning tools, but the proportion of defective lakop sapu ijuk production is 6.2% of the total production, whereas the company's set standard for defective products is 5%, resulting in financial losses. In this study, the Root Cause Analysis method was employed to identify the root causes and propose improvements. Through Fault Tree Analysis, it was found that the most significant root cause is the lack of maintenance and replacement of machines. The suggested solutions through the Process Decision Program Chart are to improve the maintenance and replacement schedule, provide additional training for workers and operators, and enhance the supervision system and SOP socialization for better production outcomes in the future.